2019
DOI: 10.1016/j.ecolecon.2019.02.002
|View full text |Cite
|
Sign up to set email alerts
|

“Something inside me has been set in motion”: Exploring the psychological wellbeing of people engaged in sustainability initiatives

Abstract: The role of sustainability initiatives and niche groups in transitions towards sustainability has received a good deal of attention. However, little is known about the people who make up these groups. This paper discusses their psychological wellbeing -a concept that comprises six elements: self-acceptance, personal growth and development, purpose in life, environmental mastery, autonomy, and positive relations with others. In the study we performed 46 semi-structured interviews with people from 11 sustainabil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0
7

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(31 citation statements)
references
References 50 publications
(71 reference statements)
0
18
0
7
Order By: Relevance
“…Contrary to the notion that consumption determines well-being 9,16 , proponents of lifestyles driven by voluntary simplicity argue for a "double dividend": simultaneously reducing consumption while enhancing wellbeing 9,16,40 . Previous studies suggest that participation in grassroots initiatives could be linked to increased awareness and pro-environmental behaviors, while supporting individuals in the pursuit of well-being [46][47][48] and quality of social life 40,41,44 .…”
Section: Sustainability-oriented Grassroots Initiativesmentioning
confidence: 99%
See 1 more Smart Citation
“…Contrary to the notion that consumption determines well-being 9,16 , proponents of lifestyles driven by voluntary simplicity argue for a "double dividend": simultaneously reducing consumption while enhancing wellbeing 9,16,40 . Previous studies suggest that participation in grassroots initiatives could be linked to increased awareness and pro-environmental behaviors, while supporting individuals in the pursuit of well-being [46][47][48] and quality of social life 40,41,44 .…”
Section: Sustainability-oriented Grassroots Initiativesmentioning
confidence: 99%
“…A recent qualitative study derived from the same project (GLAMURS) presented evidence of a positive association between grassroots membership and several dimensions of well-being: selfacceptance, personal growth, purpose in life, environmental mastery, autonomy, and positive relations with others 46 . Our findings provide quantitative evidence that lower consumption CF and higher life satisfaction are compatible for members of grassroots initiatives.…”
Section: Life Satisfaction Of Initiative Members and Non-membersmentioning
confidence: 99%
“…Individuals' values are also substantially and directly related to their subjective well-being for life satisfaction [32][33][34]. Mock et al [35] have shown that psychological wellbeing (e.g., subjective well-being) is a significant aspect of people engaged in sustainability initiatives. Nevertheless, studies on sustainable crowdfunding have largely neglected the causes and effects of value, attachment, and subjective well-being.…”
Section: Introductionmentioning
confidence: 99%
“…Previous findings (Hill et al, 2019;Briggs, 2012) discovered that psychological well-being influenced a person's mental health; hence, it has to be prepared from early age as preventive and developmental efforts (Mock et al, 2019). Therefore, counseling and guidance services should offer positive impact on pre-service teacher's personal growth.…”
Section: The Developed Guidance and Counseling Servicesmentioning
confidence: 99%
“…Psychological well-being has become major discussion in Indonesia this decade. Many scholars have assumed that psychological well-being is a factor supporting someone's future happiness, which is stimulated by individual's learning in dealing with problem or environment (Mock et al, 2019), and affected by their experience and education (Ryff, 2014;Ryff and Heidrich, 1997).…”
Section: Introductionmentioning
confidence: 99%